2011
DOI: 10.1002/eji.201041098
|View full text |Cite
|
Sign up to set email alerts
|

The enigma of CD4‐lineage specification

Abstract: CD4 T cells are essential for defenses against pathogens, and control the functions of most cells involved in the immune response. Although CD4 T cells generally recognize peptide antigens bound to MHC-II molecules, important subsets are restricted by other MHC or MHC-like molecules, including CD1d-restricted ‘invariant’ iNK T cells. This review discusses recently identified nodes in the transcriptional circuits that are involved in controling CD4 T cell differentiation, including the commitment factor Thpok a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Our results suggest that the Cd4 locus may undergo enhancer switching in part similar to Cd8a / Cd8b1 loci, and that CD4 expression may actively be maintained by a post-selection stage-specific enhancer that requires the 1.5 kb sequence. Although transcription factor requirements for CD4 versus CD8 lineage decision have been explained in large part by Gata3, ThPOK, and Runx3/CBFβ (3, 2830), there may be additional factors which also play key roles in the cell fate decision process presumably through regulation of sustained Cd4 expression. The putative post-selection enhancer appears likely to account for Ep4-independent CD4 expression following MHCII-restricted selection (8).…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that the Cd4 locus may undergo enhancer switching in part similar to Cd8a / Cd8b1 loci, and that CD4 expression may actively be maintained by a post-selection stage-specific enhancer that requires the 1.5 kb sequence. Although transcription factor requirements for CD4 versus CD8 lineage decision have been explained in large part by Gata3, ThPOK, and Runx3/CBFβ (3, 2830), there may be additional factors which also play key roles in the cell fate decision process presumably through regulation of sustained Cd4 expression. The putative post-selection enhancer appears likely to account for Ep4-independent CD4 expression following MHCII-restricted selection (8).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Runx3 for cytotoxic genes, it is not yet clear to which extent Thpok itself contributes to the expression of CD4-lineage genes, including its own [15, 25, 42, 43]. However, genetic studies have identified several transcription factors important for CD4 T cell generation, and thus candidates for a specification function; these include Gata3, the DNA-binding protein Tox, and E proteins E2A and HEB [4446].…”
Section: Lineage Specificationmentioning
confidence: 99%
“…How TCR specificity determines thymocyte lineage fate during positive selection is best described by the kinetic signaling model 4 - 7 which proposes that lineage fate is determined by whether TCR signaling persists throughout positive selection or is disrupted, allowing positively selected thymocytes to then be signaled by cytokines. In this perspective, persistent TCR signaling induces expression of ThPOK 8 - 10 , the CD4-helper lineage-specifying transcription factor, whereas cytokine signaling induces expression of Runx3d 11 - 13 , the CD8-cytotoxic lineage-specifying factor 4 , 11 - 15 . Thus, the kinetic signaling model stipulates that CD8 lineage fate is signaled by cytokines and not by TCRs which instead signal CD4 lineage fate.…”
Section: Introductionmentioning
confidence: 99%